ANALISIS PEMASARAN DURIAN DI KAWASAN BOULEVARD MANADO - Langi, Merry J.J.; Saerang, Apriano; Mose, Yuliana (KONTAN: Jurnal Ekonomi, Manajemen dan Bisnis, 2023)
In the city of Manado, precisely in the Manado Boulevard area, it became one of the places for durian traders to sell durian fruit. The Boulevard area is already well-known as a place for durian connoisseurs because apart from easy access it is also a gathering place for traders from several areas such as from Minahasa Regency and Bolaang Mongondow to sell durian fruit in the Boulevard Area. Research Objectives Knowing the factors in the marketing of durian fruit in the Boulevard Manado area, Knowing how the buying and selling pattern of durian fruit marketing. The research was carried out. Namely by describing the fruit marketing carried out by the respondents. The data obtained from durian fruit traders in the Manado Boulevard area at the time of the research and processed using SWOT analysis. The factors in marketing in the Boulevard Area are the products offered are local durians. Affordable Trader prices and Durian Places are sold by durian traders along the main road of the Manado Boulevard Area. IFE matrix, the score of the strength factor and the weakness factor is 3.94, the strength and weakness factor of Durian in the Manado Boulevard Area is in a very strong internal position. In the EFE matrix, that Durian Marketing in the Manado Boulevard Area can take advantage of existing opportunities and can survive threats in its industrial market.ABSTRAKDi kota Manado tepatnya di kawasan Boulevard Manado, menjadi salah satu tempat bagi para pedagang durian untuk berjualan buah durian. Kawasan Boulevard sudah terkenal sebagai tempat bagi para penikmat buah durian dikarenakan selain tempat akses yang mudah juga tempat berkumpulnya para pedagang dari beberapa daerah seperti di beberapa kabupaten/kota,menjual buah durian di Kawasan Boulevard tersebut. Tujuan Penelitian mengetahui factor-faktor dalam pemasaran buah durian tersebut, mengetahui bagaimana pola jual beli. Penelitian ini dilaksanakan pada bulan Februari sampai Maret 2021. Data yang diperoleh kemudian dianalisis dengan menggunakan analisis Deskriptif Kualitatif yaitu dengan mendeskripsikan pemasaran buah yang dilakukan oleh responden. Data-data yang diperoleh pada saat penelitian berlangsung dan diolah menggunakan analisis SWOT. Adapun factor-faktor dalam pemasaran di Kawasan Boulevard yaitu Produk yang ditawarkan adalah Durian Lokal. Harga Pedagang. Pemasaran Durian Di Kawasan Boulevard Manado berada pada posisi internal yang begitu kuat. Pada matriks EFE, faktor peluang dan ancaman memiliki total skor 3,35.